1983
DOI: 10.1016/s0006-3495(83)84361-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent tandem phycobiliprotein conjugates. Emission wavelength shifting by energy transfer

Abstract: A fluorescent tandem phycobiliprotein conjugate with a large Stokes shift was prepared by the covalent attachment of phycoerythrin to allophycocyanin. The efficiency of energy transfer from phycoerythrin to allophycocyanin in this disulfide-linked conjugate was 90%. A distinctive feature of this phycocyanin conjugate is the wide separation between the intense absorption maximum of phycoerythrin (epsilon = 2.4 x 10(6) cm-1 M-1 at 545 nm) and the fluorescence emission maximum of allophycocyanin (660 nm). Energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
2
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 8 publications
(5 reference statements)
0
56
2
1
Order By: Relevance
“…1 The high fluorescence yield of the biliproteins contributes to the high-efficiency energy transfer, which, in principle, also makes them excellent candidates for fluorescent biomarkers. [6][7][8] There are four types of chromophores covalently attached to the phycobiliproteins, namely, phycocyanobilin (PCB), phycoerythrobilin (PEB), phycoviolobilin (PVB) and phycourobilin (PUB). 3,9,10 All are derived from heme, which is first oxidatively cleaved by heme oxygenase, HO1, to biliverdin, 11 followed by an enzymatic reduction to PCB through the function of PCB: ferredoxin oxidoreductase, PcyA; 12 if PEB is formed, the PEB:…”
Section: Introductionmentioning
confidence: 99%
“…1 The high fluorescence yield of the biliproteins contributes to the high-efficiency energy transfer, which, in principle, also makes them excellent candidates for fluorescent biomarkers. [6][7][8] There are four types of chromophores covalently attached to the phycobiliproteins, namely, phycocyanobilin (PCB), phycoerythrobilin (PEB), phycoviolobilin (PVB) and phycourobilin (PUB). 3,9,10 All are derived from heme, which is first oxidatively cleaved by heme oxygenase, HO1, to biliverdin, 11 followed by an enzymatic reduction to PCB through the function of PCB: ferredoxin oxidoreductase, PcyA; 12 if PEB is formed, the PEB:…”
Section: Introductionmentioning
confidence: 99%
“…Forster established that the ET efficiency is proportional to the inverse sixth power of the distance between the two chromophores. Thus, fluorescence resonance ET has been used extensively as a spectroscopic ruler for biological structures (13), and ET-coupled tandem phycobiliprotein conjugates have found wide application as unique fluorescent labels (14). Earlier, we showed that polycationic heterodimeric fluorophores that exploit ET and that have high affinities for double-stranded DNA offer advantages over monomeric fluorophores in multiplex fluorescence-labeling applications (15)(16)(17).…”
mentioning
confidence: 99%
“…Phycobiliproteins, a class of light-harvesting proteins that enhances the efficiency of photosynthesis are found in many species of algae [99]. Phycobiliproteins have high extinction coefficients and quantum yields.…”
Section: Tandem Dyesmentioning
confidence: 99%
“…The molecular sizes can be large, with R-phycoerythrin (RPE) at 240 kDa containing 34 bilin fluorophores. With its high molar absorption coefficient at a broad range of absorbance wavelengths between 470 nm and 550 nm, phycoerythrin (PE) can be coupled as an energy donor to a range of potential acceptor molecules, including Allophycocyanine (APC, k em = 660 nm) [99,100], Cyanine dyes (Cy5, k em = 670 nm or Cy7, k em = 767 nm) [101], and Alexa Fluor dyes (Alexa Fluor 647, k em = 667 nm) [102]. When excited at an excitation wavelength of 488 nm, energy transfer of the tandem dyes produces large Stokes shifts with emission wavelengths that can be easily resolved from PE (k em = 575 nm) or fluorescein (k em = 518 nm) [103].…”
Section: Tandem Dyesmentioning
confidence: 99%